Comportamento morfológico e genético de cultivares de mamoneira em condições de baixas altitudes nos tabuleiros costeiros de Sergipe - Ramos, Angélica Maria (2008)
The planted area of castor oil in exploration occurs in a sustainable manner, it s necessary the use of plants improved and adapted to the region of cultivation, reducing costly and degrading agricultural practices, providing the identification and acquisition of genetically superior material. This study aimed to evaluate the behavior and genetic parameters between vegetative and reproductive morphology characters of cultivars of castor beans, in low altitudes in the Coastal Tableland of Sergipe. It had been evaluated cultivars of castor bean (CNPAM 2001-42; CNPAM 2001-48; CNPAM 2001-49; CNPAM 2001-50; CNPAM 2001-57; CNPAM 2000-79; CSRN 379; CSRN 142 and CSRD 2), in the Field Trial Jorge Prado Sobral, Nossa Senhora das Dores and in the Umbaúba Field Trial. The experiment was conducted from May 30, 2007 to February 2008. The experimental design was a randomized blocks, with nine varieties of castor beans and five repetitions. Each plot was composed of two rows of 10 m in length, usually for evaluation using 16 plants per plot. The spacing of planting was 1 m between plants and between rows. Characteristics evaluated: plant height (AP); height of the stem (AC), stem diameter (DC), flowering (FLOR), length of the racemes (CR); length of the stalk (CP), number of fruits (NF); total weight of fruit (PTF), length of the fruit (CF); total weight of seeds (PTS), length of seeds (CS), width of seeds (LS); productivity of fruits (PRODF), and productivity of seeds (PRODS) and oil content seed (TOLEO). Based on the average of cultivars for each feature, was performed the analysis of variance, and the averages compared by Tukey test. From the hopes of the mean squares were calculated the heritability in the narrow sense and the genetic variation coefficient (CVg). The correlation coefficient genotypic (rge) was obtained by covariances analysis combining the characteristics evaluated in pairs in every possible way. All tests were conducted by the GENES Program. In the theoretical framework are shown the conceptual aspects that direct the conduct of this study, such as those related to the sustainability of agroecosystems and culture of castor oil. In the following chapters are made approaches about the behavior of the castor bean cultivars with regard to traits of interest for the breeding of culture, especially the cultivars CNPAM 2001-57, CNPAM 2000-79 and CNPAM 2001-50, the first only in Umbaúba and the last two in both local, and are discussed genetic parameters between vegetative and reproductive characters, beeing possible to observe that there is variability in cultivars to the flowering and height of the stem characteristics in two places; plant height, stem length, seed length, width and length seed of the fruit in Nossa Senhora das Dores and stem diameter, number of fruits and fruit productivity, in Umbaúba.